Social relationships and survival in the older adult cohort - Mariangela Uhlmann Soares; Luiz Augusto Facchini; Fúlvio Borges Nedel; Louriele Soares Wachs; Marciane Kessler; Elaine Thumé (Universidade de São Paulo, 2021)
Objective: to verify the influence of social relations on the survival of older adults living in southern Brazil. Method: a cohort study (2008 and 2016/17), conducted with 1,593 individuals aged 60 years old or over, in individual interviews. The outcomes of social relations and survival were verified by Multiple Correspondence Analysis, which guided the proposal of an explanatory matrix for social relations, the analysis of survival by Kaplan-Meier, and the multivariate analysis by Cox regression to verify the association between the independent variables. Results: follow-up was carried out with 82.5% (n=1,314), with 46.1% being followed up in 2016/17 (n=735) and 579 deaths (36.4%). The older adults who went out of their homes daily had a 39% reduction in mortality, and going to parties kept the protective effect of 17% for survival. The lower risk of death for women is modified when the older adults live in households with two or more people, in this case women have an 89% higher risk of death than men. Conclusion: strengthened social relationships play a mediating role in survival. The findings made it possible to verify the importance of going out of the house as a marker of protection for survival.